Exponential synchronization of Markovian jumping chaotic neural networks with sampled-data and saturating actuators. (May 2017) - Rakkiyappan, R.; Preethi Latha, V.; Zhu, Quanxin; Yao, Zhangsong
Abstract: This paper deals with the problem of exponential synchronization of Markovian jumping chaotic neural networks with saturating actuators using a sampled-data controller. By constructing a proper Lyapunov–Krasovskii functional (LKF) with triple integral terms, and employing Jensen's inequality, some new sufficient conditions for the exponential synchronization of considered chaotic neural networks are derived in terms of linear matrix inequalities (LMIs). The obtained LMIs can be easily solved by any of the available software. Finally, the numerical examples are provided to demonstrate the effectiveness of our theoretical results.